Interventions to improve the quality of maternal care in Ethiopia: a scoping review - Birhane, Binyam Minuye; Assefa, Yibeltal; Belay, Demeke Mesfin; Nibret, Gedefaye; Munye Aytenew, Tigabu; Liyeh, Tewachew Muche; Gelaw, Kelemu Abebe; Tiruneh, Yenework Mulu (Frontiers in Global Women's Health, 2024)
Introduction Quality improvement interventions have been part of the national agenda aimed at reducing maternal and neonatal morbidities and mortality. Despite different interventions, neonatal mortality and morbidity rates remain steady. This review aimed to map and synthesize the evidence of maternal and newborn quality improvement interventions in Ethiopia. Methods A scoping review was reported based on the reporting items for systematic reviews and meta-analysis extensions for the scoping review checklist. Data extraction, collation, and organization were based on the Joanna Briggs Institute manual of the evidence synthesis framework for a scoping review. The maternal and neonatal care standards from the World Health Organization and the Donabedian quality of health framework were used to summarize the findings. Results Nineteen articles were included in this scoping review. The review found that the studies were conducted across various regions of Ethiopia, with the majority published after 2013. The reviewed studies mainly focused on three maternal care quality interventions: mobile and electronic health (eHealth), quality improvement standards, and human resource mobilization. Moreover, the reviewed studies explored various approaches to quality improvement, such as providing training to healthcare workers, health extension workers, traditional birth attendants, the community health development army, and mothers and supplying resources needed for maternal and newborn care. Conclusion In conclusion, quality improvement strategies encompass community involvement, health education, mHealth, data-driven approaches, and health system strengthening. Future research should focus on the impact of physical environment, culture, sustainability, cost-effectiveness, and long-term effects of interventions. Healthcare providers’ knowledge, skills, attitudes, satisfaction, and adherence to guidelines should also be considered.